OPTIMAL MAINTENANCE OPERATIONS USING AN RFID-BASED MONITORING SYSTEM - Park, Sangjun; Hong, Ki-sung; Lee, Chulung (International Journal of Industrial Engineering: Theory, Applications and Practice, 2015)
In this paper, we introduce moreaggressive pull-based inventory replenishing model called as ‘“Make toConsume” (MTC)’. Ournew model extends the previous safety stock programbased on the “Make to Stock”model, as MTC allows sharing extended consumptioninformation from customer manufacturing lines through RFID applications. Our findings indicate that, in thesemiconductor industry, supplying RFID-attachedchemical filters is beneficialto venders in terms of manual and less visual replacementdecision making in today practice. The benefits of MTC can be extended to both, the venderand buyer. The filter vender is able to minimize safety stock when thesemiconductor manufacturers share their expected filter life time andconsumption quantity of each line. From a semiconductor manufacturer perspective, theoptimized filter replacement time decision contributes to reducing thefilter purchase cost, aswell as the filter supply shortage risk.